The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s13023-019-1072-y
|View full text |Cite
|
Sign up to set email alerts
|

A step-wise approach for establishing a multidisciplinary team for the management of tuberous sclerosis complex: a Delphi consensus report

Abstract: Background Tuberous sclerosis complex (TSC) is a rare autosomal dominant genetic disorder associated with mutations in TSC1 and TSC2 genes, upregulation of mammalian target of rapamycin signaling, and subsequent tumor formation in various organs. Due to the many manifestations of TSC and their potential complications, management requires the expertise of multiple medical disciplines. A multidisciplinary care approach is recommended by consensus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 37 publications
1
45
0
Order By: Relevance
“…Despite this imbalance between care need and care provision, individuals in this study reported satisfaction with how their disease was treated and monitored. Furthermore, the transition from paediatric to adult TSC care was an important area of concern ( 23 ). Although this phase is generally considered challenging or difficult ( 24 ), our results showed a smooth process in almost half of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this imbalance between care need and care provision, individuals in this study reported satisfaction with how their disease was treated and monitored. Furthermore, the transition from paediatric to adult TSC care was an important area of concern ( 23 ). Although this phase is generally considered challenging or difficult ( 24 ), our results showed a smooth process in almost half of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the care of TSC is associated with increased health care resource utilization as well as costs and the condition itself has profound impacts on quality of life. [12][13][14][15] Given the recent development of a comprehensive TSC clinic at our center, we aimed to better understand the care delivered to children with TSC before being seen in our TSC clinic to determine which gaps in surveillance of TSC care existed by examining whether the 2012 Tuberous Sclerosis Complex Consensus Recommendations were being followed. Of note, a revision to TSC guidelines is anticipated in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Although a multidisciplinary approach to TSC care has been recommended, access to specialty clinics may be limited for some patients due to a variety of factors (i.e., social, geographic, economic, etc.). 13 It is essential to identify which gaps in care exist so that surveillance and treatment for individuals with TSC can be optimized, regardless of the care delivery model in place.…”
Section: Discussionmentioning
confidence: 99%
“…The important role of multidisciplinary teams in looking after a range of chronic conditions is well established [22] and is recognised as crucial to the diagnosis and management of rare disease in key planning documents including all three French national plans for rare diseases [23,24,25] and the WA Framework. A couple of recent studies have explored more deeply the importance of multidisciplinary teams in the care provision of rare diseases requiring care from up to 10 different medical specialists being type I gaucher disease and tuberous sclerosis complex [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…These requirements reflect the desire from focus group participants to have a care plan for their condition developed with their input, and to receive strong medical oversight for their condition. The Auvin et al study [27] reported that a care coordinator or case manager, such as a nurse of other professional, was considered the number one factor in enabling a multi-disciplinary team to function reflecting the difficulties perceived by clinicians in managing patient care.…”
Section: Discussionmentioning
confidence: 99%